PERAN PENDIDIKAN DALAM MENDORONG MODERASI BERAGAMA DI TORAJA UNTUK MENJAGA KEHARMONISAN ANTARUMAT DALAM KONTEKS SOSIAL DAN BUDAYA LOKAL - Elfiana Toding Kallang; Yosika Sindy Embong Bulan; Selin Tibarrang; Maria Ipen; Seri Lolongan (JIP: Jurnal Ilmu Pendidikan, 2025)
This article discusses the role of education in encouraging religious moderation in Toraja, a region rich in religious tradition and diversity. Religious moderation, which prioritizes tolerance, mutual respect and avoiding extremism, is important in maintaining harmony between religious communities amidst local social and cultural dynamics. Through educational approaches, both formal and non-formal, it is hoped that the values ​​of religious moderation can be instilled from an early age in the younger generation. This research analyzes various educational strategies that can be implemented by educational institutions in Toraja to foster inclusive attitudes and respect for differences, as well as how these values ​​can strengthen relations between religious believers in everyday life. The research results show that education based on local cultural values, such as mutual cooperation and mutual respect, has a vital role in supporting the creation of a moderate and harmonious society. This article also offers recommendations for integrating religious moderation in the educational curriculum in Toraja.